Ethnicity in politics: notes on the peruvian case - Olivera, Luis (2017)
This article addresses a subject of singular relevance in the current debate regarding the role, weight and dimension that ethnicity plays in organizing and reforming politics in the 21st century in Peru. Based upon the Peruvian process, an analysis considering political science, history and communication allows the paper to discuss the presence of Peru’s indigenous peoples in a historical continuity from their natural adaptation to the Andes, through the Inca expansion, the devastation of the conquest, the ruptures of colonialism, the continuities of the republic, to the fallacious proposition of an ethnocacerist identity. It also addresses the particular manifestation of the ethnic concept in Peru today, as a novelty driven by the International Monetary Fund and the World Bank. Finally, the article points to the challenge of intercultural communication in an objectively multilingual and multicultural society.